Serum Levels of Cross-linked N-Telopeptide of Type I Collagen before and After Non-surgical Periodontal Therapy in Type 2 Diabetic Patients with Chronic Periodontitis - Wael A. Kzar (Journal of Global Pharma Technology, 2019)
Background: Diabetes mellitus is a major risk factor for chronic periodontitis (CP) and hyperglycemia has an important role in the enhancement of the severity of the periodontitis. It has been reported that the progression of CP causes shifting of the balance between bone formation and resorption toward osteoclastic resorption, and this will lead to the release of collagenous bone breakdown products into the local tissues and the systemic circulation. Cross-linked N-telopeptide of type I collagen (NTx) is the amino-terminal peptides of type I collagen which is released during the process of bone resorption. This study was conducted to determine the effects of nonsurgical periodontal therapy on serum level of NTx in type 2 diabetic patients with chronic periodontitis (CP) and in systemically healthy patients with CP and to correlate NTx level with the clinical periodontal parameters in the studied groups. Materials and methods: The studied sample consisted of ninety subjects of both genders with an age range (35-55). They were divided into three groups, the first group consisted of 30 subjects with healthy periodontium and systemically healthy (control group), the second group consisted of 30 patients having chronic periodontitis and type 2 diabetes mellitus (CPDM) group, and the third group consisted of 30 patients with chronic periodontitis only and systemically healthy (CP) group. All the subjects enrolled in this study were with normal body mass index. The clinical periodontal parameters measured were plaque index (PLI), gingival index (GI), probing pocket depth (PPD), and relative attachment level (RAL). The blood samples were collected from all individuals and examined to measure the serum level of NTx using enzyme-linked immune sorbent assay (ELISA). Patients with chronic periodontitis were treated with scaling and root planning (SRP) and recalled for further measurements of the clinical periodontal parameters and collection of the blood sample to measure the serum level of NTx after eight weeks. Results: All the clinical periodontal parameters at the baseline were higher than that after treatment. PPD and RAL were highest in CPDM group followed by CP. Regarding the level of NTx at the baseline; it was highest in CPDM group followed by CP group then the control group. After treatment, results revealed a reduction in NTx level for both CPDM and CP groups. Regarding the correlation between the clinical periodontal parameters and NTx level, the results revealed almost a non-significant weak positive correlation. Conclusions: SRP is an impactful procedure and results in the improvement of all the clinical periodontal parameters and reduction in the serum level of cross-linked N-telopeptide of type I collagen which could be considered as a good bone resorption marker in the studied groups.Keywords: Periodontitis, Type 2 diabetes mellitus, Cross-linked N-telopeptide of type I collagen, Nonsurgical periodontal therapy.